Human Resource Management: A Critical Approach - Collings, David G. (Routledge, 2012)
The book explores all the central themes and concepts of HRM theory and practice, and introduces the most important issues influencing contemporary practice in a wide range of organizational contexts. It systematically examines the main functional areas of HRM, and engages with a number of key contemporary issues for both scholars and practitioners.